Tree human resources (HR) model of human resource development in higher education - Amir Tengku Ramly; Budi Handrianto; Syaiful .Syaiful (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Research related to human resource development models in the world of education is very important, because the world of education is one of the determinants of the quality of HR assets. This research aims to find the HR model that best suits the development of Human Resources (HR) in higher education. The research uses qualitative methods. The type of research used is R&D (Research & Development). In the first year using the Analysis and Design approach from the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Data collection was carried out through a literature review study of 90 articles indexed by Scopus, Sinta 1, Sinta 2, and interviews with 15 experts from the academic and professional world. This research was analyzed using the SWOT Analysis and FGD approach. The results of this research found a prototype tree-based HR model and important variables that were mapped to the tree structure, namely root variables, stem variables, and fruit/leaf variables. This research is used to improve the quality of higher education human resources. This has implications for improving the quality of lecturers both in self-development and teaching in higher education, which has an impact on the quality of students and Indonesia's human resource assets.